Does Increasing Public Hospital Financial Autonomy Improve Performance? A Study of Indonesian Public Hospitals - Fitri HANDAYANI; Hasan BASRI; Heru FAHLEVI (Management and Economics Review, 2019)
This study aims to compare the financial and non-financial performance of Indonesian public hospitals after gaining improved autonomy in financial management (Badan Layanan umum/ BLU or Public Service Agency/ PSA). It is conducted in two public hospitals in Banda Aceh City, Indonesia. Qualitative research design and descriptive analysis were undertaken to obtain a clearer picture of the performance and to provide a comparative analysis. The financial performance analysis is measured by using trend analysis, profitability ratio, cost recovery rate, and independence level. The non-financial performance analysis is measured by using BOR (Bed Occupancy Ratio), TOI (Turn over Interval), BTO (Bed Turn Over), ALOS (Average Length of Stay), GDR (Gross Death Rate), and NDR (Net Death Rate). The results show divergent results. There is an increase in revenue and profit after gaining BLU, but profitability, cost recovery rate, and independence level have decreased. The ratios of BOR, TOI, and NDR after BLU has changed slightly. However, the BTO, ALOS, and GDR after BLU are far above the criteria/standard of hospital service performance.